What can the location of biogas plants tell us about agricultural change? A Case Study from the Czech Republic - Dan Van Der Horst; Stanislav Martinát; Josef Navrátil; Petr Dvořák; Petra Chmielová (DETUROPE)
Facilities for generating renewable energy form important elements in the rural landscape of the Czech Republic. The distribution of these facilities is highly uneven due to various natural and socio-economic factors. In our paper, we are focusing our attention on one of the important facilities for the generation of renewable energy in the Czech Republic; anaerobic digestion (AD) plants. In 2016, more than five hundred AD plants could be found in the country with a total installed capacity of 360 MW. By means of analyses of data on location of individual AD plants, quality of soils, size of agricultural farms (in which majority of AD plants is incorporated) we found that agricultural AD plants in the Czech Republic tend to concentrate in areas with larger agricultural farms and also in areas with average and slightly below average conditions for agricultural activities. Core areas where agricultural AD plants are the most densely located were also identified. In these areas, large farms with AD plants tend to crowd out smaller farms. Pressure to grow maize for ADs significantly competes here with growing of other agricultural crops for food. This finding is in strong contradiction with the official national agricultural policy where support for small farms is systematically emphasized. Core areas with AD plants make a belt that mostly covers sub-mountainous central parts of the Czech Republic where traditional agricultural plants are now significantly being displaced by maize to feed AD plants.